Research on jamming technology of frequency-stepping millimeter-wave guided seeker - Xiang Zhengshan (Dianzi Jishu Yingyong, 2021)
Aiming at the problem of how to implement effective countermeasures against frequency-stepping millimeter-wave precision guided weapons, this paper analyzes the working principle of two-dimensional imaging of frequency-stepping millimeter-wave guided seekers, constructs the two-dimensional imaging scene of frequency-stepping millimeter-wave guided seekers, and carries out systematic and comprehensive simulation on imaging processing of frequency-stepping millimeter-wave guided seekers and various jamming techniques. The simulation results show that no matter whether the jamming source is located in the range of antenna beam coverage of the seeker or not, both incoherent and coherent jamming can jam frequency-stepping millimeter-wave guided seekers. The energy of incoherent jamming is more dispersed, and the energy of coherent jamming is more concentrated. Therefore, a compound jamming strategy of inverse gain and active jamming is proposed in this paper, which can realize jamming of frequency-stepping millimeter-wave guided seeker and simultaneously realize self -protection of the jamming source.